A lightweight authentication and key agreement scheme for smart grid. (February 2017) - Yan, Lili; Chang, Yan; Zhang, Shibin
Smart grid is a modernized electrical grid. It is used to collect information about behaviors of suppliers and consumers and improve the efficiency, reliability, and economics of electricity. Recently, advanced metering infrastructure is proposed as a critical part of the smart grid. The security of advanced metering infrastructure is special importance for smart grid. In order to achieve data confidentiality, privacy, and authentication in advanced metering infrastructure, a lightweight authentication and key agreement scheme is proposed in this article. The scheme provides mutual authentication, key agreement, key refreshment, and multicast mechanism which can prevent various attacks. Furthermore, we analyze the security and performance of the scheme. The analysis shows that the proposed scheme is suitable for smart grid.